A cadmium-free and lead-free high-thermal-conductivity composite solder and a preparation method thereof

CN122895745APending Publication Date: 2026-10-13CHANGSHU HUAYIN FILLER METALS
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611272093.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-21
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

根据声学失配模型,此类界面声子透射系数通常不足0.1,超过90%的热量在界面处被反射,导致整体热导率反而低于SAC305

Benefits of technology

[0015]本发明相较于现有技术,其有益效果为:本发明通过聚多巴胺和3-巯基丙基三甲氧基硅烷对h-BNNSs(六方氮化硼纳米片)进行界面化学修饰,为镓铟微滴提供化学锚定位点,构建了镓铟液态声子耦合桥。该桥联层在h-BNNSs与Sn基体之间充当声子频率过渡介质,降低了传统陶瓷/Sn界面的声子失配热障,使界面声子有效传递率有效提升。同时,本发明可在复合颗粒添加量1.6-2.2 wt%的低质量分数下,使得复合钎料的拉伸强度和热导率较SAC305均有较为明显的提升。此外,本发明钎料不含铅、镉等有害元素,避免了对焊接操作人员的健康危害和环境污染。

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The application discloses a kind of cadmium-free lead-free high-thermal-conductivity composite brazing filler metal and preparation method thereof, belong to brazing filler metal preparation technical field, including matrix alloy powder and composite modified phase;The matrix alloy powder includes the following components according to mass percentage:Ag 2.8‑3.5%;Cu 0.5‑0.8%;Sb 4.5‑5.5%;Ni 0.05‑0.12%;The balance is Sn;Composite modified phase includes gallium-indium supported type hexagonal boron nitride composite particles, gallium-indium supported type hexagonal boron nitride composite particles include hexagonal boron nitride, composite surface modification layer located on the surface of hexagonal boron nitride, and gallium-indium alloy droplet loaded on the composite surface modification layer;The composite surface modification layer is formed by 3-mercapto propyl trimethoxysilane grafting after polydopamine transition layer is formed on the surface of hexagonal boron nitride by hydrochloric acid dopamine.The tensile strength and brazing filler metal thermal conductivity of the present application are obviously improved compared with SAC305 under the condition that the amount of composite particles is 1.6‑2.2 wt%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of solder preparation technology, specifically to a cadmium-free and lead-free high thermal conductivity composite solder and its preparation method. Background Technology

[0002] Traditional lead-free solders generally suffer from the following technical problems: (1) Taking SAC305 as an example, its thermal conductivity is only 50-60 W / m·K, which is much lower than that of pure copper. The reason is that in order to obtain sufficient mechanical properties, elements such as Ag and Cu are generally introduced. However, this will also lead to the formation of more Ag3Sn, Cu6Sn5 intermetallic compounds and solid solution atoms in β-Sn. These heterogeneous phases and point defects constitute dense electron and phonon scattering centers, which compress the mean free path of heat-carrying particles and thus affect the thermal conductivity.

[0003] (2) When high thermal conductivity ceramic fillers are introduced, the Sn matrix and the ceramic phase are only in contact by weak van der Waals forces, forming a typical phonon mismatch interface. According to the acoustic mismatch model, the phonon transmission coefficient of such interfaces is usually less than 0.1, and more than 90% of the heat is reflected at the interface, resulting in an overall thermal conductivity that is lower than that of SAC305.

[0004] Based on this, the present invention designs a cadmium-free and lead-free high thermal conductivity composite solder and its preparation method to solve the above problems. Summary of the Invention

[0005] In view of the above-mentioned shortcomings of the existing technology, the present invention provides a cadmium-free and lead-free high thermal conductivity composite solder and its preparation method.

[0006] To achieve the above objectives, the present invention provides the following technical solution: A cadmium-free and lead-free high thermal conductivity composite solder comprises a matrix alloy powder and a composite modified phase; The matrix alloy powder comprises the following components by mass percentage: Ag 2.8-3.5%; Cu 0.5-0.8%; Sb 4.5-5.5%; Ni 0.05-0.12%; The remainder is Sn; The composite modified phase includes gallium indium supported hexagonal boron nitride composite particles, which include hexagonal boron nitride, a composite surface modification layer located on the surface of hexagonal boron nitride, and gallium indium alloy microdroplets loaded on the composite surface modification layer. The composite surface modification layer is formed by grafting a polydopamine transition layer onto a hexagonal boron nitride surface with dopamine hydrochloride, followed by grafting with 3-mercaptopropyltrimethoxysilane.

[0007] Furthermore, the amount of gallium indium supported hexagonal boron nitride composite particles added is 1.6-2.2% of the total mass of the matrix alloy powder.

[0008] Furthermore, the composite surface modification layer is made of a composite surface modifier, which includes 3-mercaptopropyltrimethoxysilane and dopamine hydrochloride, with a mass ratio of 3-mercaptopropyltrimethoxysilane to dopamine hydrochloride of 1:1.5-1:3.0.

[0009] To better achieve the objectives of this invention, this invention also provides a method for preparing a cadmium-free and lead-free high thermal conductivity composite solder, comprising the following steps: 1. Weigh Sn, Ag, Cu, Sb and Ni raw materials to prepare alloy melt; 2. Cool the alloy melt and atomize it to obtain a matrix alloy powder with a particle size of 15-40 μm; III. Preparation of gallium-indium supported hexagonal boron nitride composite particles, the specific steps of which include: (1) After hexagonal boron nitride is dispersed and ultrasonically exfoliated and dried, it is then dispersed in Tris buffer, dopamine hydrochloride is added, stirred at room temperature for 5-6 h, centrifuged and washed to obtain polydopamine-coated hexagonal boron nitride. (2) Add 3-mercaptopropyltrimethoxysilane to the solvent, adjust the pH to 4.5 with acetic acid, and pre-hydrolyze for 30 min; add polydopamine-coated hexagonal boron nitride, stir at 40 °C for 4 h, then centrifuge, wash and vacuum dry at 35 °C for 12 h; (3) Add gallium-indium alloy to a solvent to obtain a gallium-indium microdroplet dispersion; (4) The surface-modified hexagonal boron nitride was redispersed in a solvent; gallium indium microdroplet dispersion was slowly added under nitrogen protection and stirred for 1.5-2 h; after centrifugation, washing and drying, gallium indium supported hexagonal boron nitride composite particles were obtained. 4. Pre-disperse gallium indium supported hexagonal boron nitride composite particles in a solvent; add the matrix alloy powder to a nitrogen-protected mixer, and simultaneously add the gallium indium supported hexagonal boron nitride composite particle suspension to the mixer. After mixing, the material is dried and sieved to obtain cadmium-free and lead-free high thermal conductivity composite solder.

[0010] Furthermore, step one specifically involves: weighing Sn, Ag, Cu, Sb, and Ni raw materials, placing them in a vacuum induction melting furnace, evacuating the furnace to 30-80 Pa, maintaining this state for 5-15 minutes to remove air from the furnace; under argon protection, raising the furnace temperature to 560-610 ℃, and after the raw materials have completely melted, holding the temperature at 580-610 ℃ for 20-40 minutes, stirring at a speed of 200-300 r / min for 10-15 minutes, and letting it stand for 5-10 minutes to obtain the alloy melt.

[0011] Furthermore, in step two, the pressure of the atomizing gas is 2.0-4.5 MPa; the flow rate of the alloy melt is 5-20 kg / min; and the oxygen content in the atomization chamber is <500 ppm.

[0012] Furthermore, in step (1), the shearing treatment is carried out at 8000-12000 r / min for 25-30 min, and then ultrasonic treatment is carried out at 300-500 W power with a 5 s on and 5 s intermittent mode for 2-3 h.

[0013] Furthermore, in step four, gallium-indium microdroplet dispersion is slowly added dropwise under nitrogen protection for 20-30 min; after the addition is completed, stirring is continued for 1.5-2 h at 250-300 r / min.

[0014] Furthermore, in step four, the composite particle suspension is slowly sprayed into the mixer over 20-30 minutes, and mixing continues for 35-45 minutes after the spraying is completed.

[0015] Compared to existing technologies, the advantages of this invention are as follows: This invention uses polydopamine and 3-mercaptopropyltrimethoxysilane to chemically modify the interface of h-BNNSs (hexagonal boron nitride nanosheets), providing chemical anchoring sites for gallium-indium microdroplets and constructing a gallium-indium liquid phonon coupling bridge. This bridging layer acts as a phonon frequency transition medium between h-BNNSs and the Sn matrix, reducing the phonon mismatch thermal barrier of traditional ceramic / Sn interfaces and effectively improving the interfacial phonon transfer rate. Simultaneously, this invention can achieve a significant improvement in the tensile strength and thermal conductivity of the composite solder compared to SAC305 at a low mass fraction of 1.6-2.2 wt% composite particles. Furthermore, the solder of this invention does not contain harmful elements such as lead and cadmium, avoiding health hazards to welding operators and environmental pollution. Detailed Implementation

[0016] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are within the scope of protection of the present invention.

[0017] Example 1: A method for preparing a cadmium-free and lead-free high thermal conductivity composite solder, comprising the following steps: 1. Weigh the raw materials according to the following mass percentages: Ag 2.8%, Cu 0.8%, Sb 4.5%, Ni 0.12%, Sn 91.78%, and place them in a vacuum induction melting furnace. Evacuate the furnace to 30 Pa and maintain the vacuum for 15 min to remove air from the furnace. Under argon protection, raise the furnace temperature to 560 ℃. After the raw materials are completely melted, hold the temperature at 580 ℃ for 40 min, stir at 200 r / min for 15 min, and let stand for 5 min to obtain the alloy melt. 2. Cool the alloy melt to 350℃ and atomize it using high-purity argon gas. Collect the atomized alloy powder and sieve it under nitrogen protection to obtain a matrix alloy powder with a particle size of 15-40 μm, which is then stored under sealed conditions. The pressure of the atomizing gas is 2.0 MPa; the flow rate of the alloy melt is 5 kg / min; and the oxygen content in the atomization chamber must be <500 ppm.

[0018] III. Preparation of gallium-indium supported hexagonal boron nitride composite particles, the specific steps of which include: (1) 20 g of hexagonal boron nitride was added to a mixture of 2 L of isopropanol and water, wherein the volume ratio of isopropanol to water was 75:25; the mixture was subjected to high shear at 8000 r / min for 30 min, and then subjected to ultrasonic treatment at 300 W with 5 s on and 5 s intermittent for 3 h. After centrifugation, the precipitate was washed with water and ethanol and freeze-dried to obtain hexagonal boron nitride; 7.2 g of hexagonal boron nitride was dispersed in Tris buffer at pH 8.5, 3.0 g of dopamine hydrochloride was added, and the mixture was stirred at room temperature for 5 h. After centrifugation, the precipitate was washed with water and ethanol to obtain polydopamine-coated hexagonal boron nitride. (2) 2.0 g of 3-mercaptopropyltrimethoxysilane was added to 100 mL of a solvent with a volume ratio of ethanol to water of 95:5, and the pH was adjusted to 4.5 with acetic acid. The mixture was pre-hydrolyzed for 30 min. Polydopamine-coated hexagonal boron nitride was added, and the mixture was stirred at 40 °C for 4 h. Then the mixture was centrifuged, washed with ethanol, and vacuum dried at 35 °C for 12 h. (3) Prepare a gallium-indium eutectic alloy according to the ratio of Ga 75.5 wt% and In 24.5 wt%. Add 3.8 g of gallium-indium alloy to a mixture of ethanol and water that has been deoxygenated by nitrogen (the volume ratio of ethanol to water is 95:5). Sort the mixture with 300 W pulsed ultrasound at 20℃ for 20 min to obtain a 5 wt% gallium-indium microdroplet dispersion. (4) The surface-modified hexagonal boron nitride was redispersed in a mixture of 2 L of ethanol and water at a volume ratio of 95:5 and ultrasonically treated with 100 W power for 5 min. Under nitrogen protection, gallium indium microdroplet dispersion was slowly added dropwise for 20 min. After the addition was completed, the mixture was stirred for 2 h at 250 r / min. After centrifugation, the precipitate was washed with anhydrous ethanol and then dried at 35 °C and 300 Pa vacuum for 12 h to obtain gallium indium supported hexagonal boron nitride composite particles.

[0019] 4. Take 8.0 g of gallium-indium supported hexagonal boron nitride composite particles and pre-disperse them in 30 g of anhydrous ethanol. Sonicate them at 100W power for 5 min. Add 500 g of matrix alloy powder to a nitrogen-protected mixer and mix at 40 r / min. At the same time, slowly spray the gallium-indium supported hexagonal boron nitride composite particle suspension into the mixer over 20 min. After the spraying is completed, continue mixing for 35 min. Dry the resulting material at 35℃ and 300 Pa vacuum for 8 h. Sieve the material to obtain cadmium-free and lead-free high thermal conductivity composite solder.

[0020] According to GB / T 22588-2008, the thermal conductivity is 71.3 W / m·K, and according to GB / T 228.1-2021, the tensile strength is 47.2 MPa.

[0021] Example 2: A method for preparing a cadmium-free and lead-free high thermal conductivity composite solder, comprising the following steps: 1. Weigh the raw materials according to the following mass percentages: Ag 3.5%, Cu 0.5%, Sb 5.5%, Ni 0.05%, Sn 90.45%, and place them in a vacuum induction melting furnace. Evacuate the furnace to 80 Pa and maintain this state for 5 minutes to remove air from the furnace. Under argon protection, raise the furnace temperature to 610 °C. After the raw materials have completely melted, maintain the temperature at 610 °C for 20 minutes, stir at 300 r / min for 10 minutes, and let stand for 10 minutes to obtain the alloy melt. 2. The alloy melt is cooled to 410℃ and atomized using high-purity argon gas. The atomized alloy powder is collected and sieved under nitrogen protection to obtain a matrix alloy powder with a particle size of 15-40 μm, which is then stored under sealed conditions. The pressure of the atomizing gas is 4.5 MPa; the flow rate of the alloy melt is 20 kg / min; and the oxygen content in the atomization chamber is <500 ppm.

[0022] III. Preparation of gallium-indium supported hexagonal boron nitride composite particles, the specific steps of which include: (1) 25 g of hexagonal boron nitride was added to a mixture of 2 L of isopropanol and water, wherein the volume ratio of isopropanol to water was 75:25; the mixture was subjected to high shear at 12000 r / min for 25 min, and then subjected to ultrasonic treatment at 500 W with 5 s on and 5 s intermittent for 2 h. After centrifugation, the precipitate was washed with water and ethanol and freeze-dried to obtain hexagonal boron nitride; 7.2 g of hexagonal boron nitride was dispersed in Tris buffer at pH 8.5, 6.0 g of dopamine hydrochloride was added, and the mixture was stirred at room temperature for 5 h. After centrifugation, the precipitate was washed with water and ethanol to obtain polydopamine-coated hexagonal boron nitride. (2) 2.0 g of 3-mercaptopropyltrimethoxysilane was added to 100 mL of a solvent with a volume ratio of ethanol to water of 95:5, and the pH was adjusted to 4.5 with acetic acid. The mixture was pre-hydrolyzed for 30 min. Polydopamine-coated hexagonal boron nitride was added, and the mixture was stirred at 40 °C for 4 h. Then the mixture was centrifuged, washed with ethanol, and vacuum dried at 35 °C for 12 h. (3) Prepare a gallium-indium eutectic alloy according to the ratio of Ga 75.5 wt% and In 24.5 wt%. Add 3.8 g of gallium-indium alloy to a mixture of ethanol and water that has been deoxygenated by nitrogen (the volume ratio of ethanol to water is 95:5). Sort the mixture with 400 W pulsed ultrasound at 20℃ for 15 min to obtain a 5 wt% gallium-indium microdroplet dispersion. (4) The surface-modified hexagonal boron nitride was redispersed in a mixture of 2 L of ethanol and water at a volume ratio of 95:5 and ultrasonically treated with 300 W power for 5 min. Under nitrogen protection, gallium indium microdroplet dispersion was slowly added dropwise for 30 min. After the addition was completed, the mixture was stirred for 1.5 h at 300 r / min. After centrifugation, the precipitate was washed with anhydrous ethanol and then dried at 35 °C and 300 Pa vacuum for 12 h to obtain gallium indium supported hexagonal boron nitride composite particles.

[0023] 4. Take 11.0 g of gallium-indium supported hexagonal boron nitride composite particles and pre-disperse them in 30 g of anhydrous ethanol. Sonicate them for 3 min using 150 W power. Add 500 g of matrix alloy powder to a nitrogen-protected mixer and mix at 60 r / min. At the same time, slowly spray the gallium-indium supported hexagonal boron nitride composite particle suspension into the mixer over 30 min. After spraying, continue mixing for 45 min. Dry the resulting material at 35℃ and 300 Pa vacuum for 8 h. Sieve the material to obtain cadmium-free and lead-free high thermal conductivity composite solder.

[0024] According to GB / T 22588-2008, the thermal conductivity is 76.6 W / m·K, and according to GB / T 228.1-2021, the tensile strength is 52.5 MPa.

[0025] Example 3: A method for preparing a cadmium-free and lead-free high thermal conductivity composite solder, comprising the following steps: 1. Weigh the raw materials according to the following mass percentages: Ag 3.2%, Cu 0.7%, Sb 4.8%, Ni 0.08%, Sn 91.22%. Place them in a vacuum induction melting furnace, evacuate the furnace to 50 Pa, and maintain this state for 10 min to remove air from the furnace. Under argon protection, raise the furnace temperature to 580 ℃. After the raw materials are completely melted, hold the temperature at 600 ℃ for 30 min, stir at 250 r / min for 12 min, and let stand for 8 min to obtain the alloy melt. 2. Cool the alloy melt to 400℃ and atomize it using high-purity argon gas; collect the atomized alloy powder and sieve it under nitrogen protection to obtain a matrix alloy powder with a particle size of 15-40 μm, which is then stored under sealed conditions. The pressure of the atomizing gas is 3.5 MPa; the flow rate of the alloy melt is 10 kg / min; and the oxygen content in the atomization chamber must be <500 ppm.

[0026] III. Preparation of gallium-indium supported hexagonal boron nitride composite particles, the specific steps of which include: (1) 22 g of hexagonal boron nitride was added to a mixture of 2 L of isopropanol and water, wherein the volume ratio of isopropanol to water was 75:25; the mixture was subjected to high shear at 9000 r / min for 28 min, and then subjected to ultrasonic treatment at 400 W with 5 s on and 5 s intermittent for 2.5 h. After centrifugation, the precipitate was washed with water and ethanol and freeze-dried to obtain hexagonal boron nitride; 7.2 g of hexagonal boron nitride was dispersed in Tris buffer at pH 8.5, 4.0 g of dopamine hydrochloride was added, and the mixture was stirred at room temperature for 5 h. After centrifugation, the precipitate was washed with water and ethanol to obtain polydopamine-coated hexagonal boron nitride. (2) 2.0 g of 3-mercaptopropyltrimethoxysilane was added to 100 mL of a solvent with a volume ratio of ethanol to water of 95:5, and the pH was adjusted to 4.5 with acetic acid. The mixture was pre-hydrolyzed for 30 min. Polydopamine-coated hexagonal boron nitride was added, and the mixture was stirred at 40 °C for 4 h. Then the mixture was centrifuged, washed with ethanol, and vacuum dried at 35 °C for 12 h. (3) Prepare a gallium-indium eutectic alloy according to the ratio of Ga 75.5 wt% and In 24.5 wt%. Add 3.8 g of gallium-indium alloy to a mixture of ethanol and water that has been deoxygenated by nitrogen (the volume ratio of ethanol to water is 95:5). Sort the mixture with 350 W pulsed ultrasound at 20℃ for 18 min to obtain a 5 wt% gallium-indium microdroplet dispersion. (4) The surface-modified hexagonal boron nitride was redispersed in a mixture of 2 L of ethanol and water at a volume ratio of 95:5 and ultrasonically treated with 200 W power for 5 min. Under nitrogen protection, gallium indium microdroplet dispersion was slowly added dropwise for 25 min. After the addition was completed, the mixture was stirred for 2 h at 250 r / min. After centrifugation, the precipitate was washed with anhydrous ethanol and then dried at 35 °C and 300 Pa vacuum for 12 h to obtain gallium indium supported hexagonal boron nitride composite particles.

[0027] 4. Take 10.0 g of gallium-indium supported hexagonal boron nitride composite particles and pre-disperse them in 30 g of anhydrous ethanol. Sonicate them at 100W power for 4 min. Add 500 g of matrix alloy powder to a nitrogen-protected mixer and mix at 50 r / min. At the same time, slowly spray the gallium-indium supported hexagonal boron nitride composite particle suspension into the mixer over 25 min. After the spraying is completed, continue mixing for 40 min. Dry the resulting material at 35℃ and 300 Pa vacuum for 8 h. Sieve the material to obtain cadmium-free and lead-free high thermal conductivity composite solder.

[0028] According to GB / T 22588-2008, the thermal conductivity is 79.2 W / m·K, and according to GB / T 228.1-2021, the tensile strength is 49.8 MPa.

[0029] Comparative Example 1: Compared with Example 3, the preparation process of the gallium indium supported hexagonal boron nitride composite particles is different. The specific preparation method includes: (1) 22 g of hexagonal boron nitride was added to a mixture of 2 L of isopropanol and water, wherein the volume ratio of isopropanol to water was 75:25; the mixture was subjected to high shear treatment at 9000 r / min for 28 min, and then subjected to ultrasonic treatment at 400 W with 5 s on and 5 s intermittent mode for 2.5 h. After centrifugation, the precipitate was washed with water and ethanol and freeze-dried to obtain hexagonal boron nitride. (2) A gallium-indium eutectic alloy was prepared according to the ratio of Ga 75.5 wt% and In 24.5 wt%. 3.8 g of the gallium-indium alloy was added to a mixture of ethanol and water that had been deoxygenated by nitrogen (the volume ratio of ethanol to water was 95:5). The mixture was then subjected to 350 W pulsed ultrasonic treatment at 20℃ for 18 min to obtain a 5 wt% gallium-indium microdroplet dispersion. (3) Hexagonal boron nitride was redispersed in a mixture of 2 L of ethanol and water at a volume ratio of 95:5 and ultrasonically treated with 200 W power for 5 min. Gallium indium microdroplet dispersion was slowly added dropwise under nitrogen protection for 25 min. After the addition was completed, the mixture was stirred for 2 h at 250 r / min. After centrifugation, the precipitate was washed with anhydrous ethanol and then dried at 35 °C and 300 Pa vacuum for 12 h to obtain gallium indium supported hexagonal boron nitride composite particles.

[0030] According to GB / T 22588-2008, the thermal conductivity is 55.1 W / m·K, and according to GB / T 228.1-2021, the tensile strength is 44.3 MPa.

[0031] Comparative Example 2: Commercially available SAC305.

[0032] According to GB / T 22588-2008, the thermal conductivity is 59.7 W / m·K, and according to GB / T 228.1-2021, the tensile strength is 42.1 MPa.

[0033] The combined results of Examples 1-3 and Comparative Examples 1-2 show that the thermal conductivity and tensile strength of Examples 1-3 are higher than those of Comparative Examples 1-2, demonstrating the necessity of interfacial chemical modification. The absence of 3-mercaptopropyltrimethoxysilane and polydopamine modification in h-BNNSs affects both thermal conductivity and tensile strength. The main reason for this is: (1) The polydopamine transition layer and the mercaptosilane graft layer are the structural basis for realizing the chemical anchoring of gallium indium microdroplets. In Comparative Example 1, after omitting the above two modification steps, there is only weak physical adsorption between gallium indium microdroplets and nanosheets. During the subsequent ethanol washing, vacuum drying and low-shear powder mixing process, a large amount of adsorption occurs, and the effective gallium indium / h-BNNSs composite ratio that actually enters the solder joint is greatly reduced, making it difficult to establish the functional structure of the gallium indium liquid phonon coupling bridge.

[0034] (2) There is an inherent phonon frequency mismatch between the exposed h-BNNSs and the Sn matrix, and the interfacial thermal resistance cannot be overcome. Sn has a large atomic mass and a low lattice vibration frequency, while h-BNNSs has a small atomic mass and a high lattice vibration frequency, resulting in a very narrow overlap region in their phonon spectra. Without a gallium-indium liquid layer as a phonon frequency transition medium, the interfacial phonon transmission coefficient is less than 0.1, and more than 90% of the heat is reflected at the interface. At the same time, the exposed nanosheets undergo irreversible agglomeration in the molten solder due to interfacial energy mismatch, which reduces the effective thermal conductivity of the matrix. The combination of these two factors results in a thermal conductivity lower than that of SAC305.

[0035] (3) The exposed h-BNNSs agglomerates are only held together by van der Waals forces, resulting in low interfacial bonding strength. Under external load, local stress concentration occurs in the matrix around the rigid agglomerates. This weak interfacial region becomes a preferred initiation site and propagation channel for microcracks, leading to a decrease in the effective load-bearing capacity of the weld joint.

[0036] The above embodiments are only used to illustrate the technical solutions of the present invention, and are not intended to limit it. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features. Such modifications or substitutions will not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A cadmium-free and lead-free high thermal conductivity composite solder, characterized in that, Including matrix alloy powder and composite modified phase; The matrix alloy powder comprises the following components by mass percentage: Ag 2.8-3.5%; Cu 0.5-0.8%; Sb 4.5-5.5%; Ni 0.05-0.12%; The remainder is Sn; The composite modified phase includes gallium indium supported hexagonal boron nitride composite particles, which include hexagonal boron nitride, a composite surface modification layer located on the surface of hexagonal boron nitride, and gallium indium alloy microdroplets loaded on the composite surface modification layer. The composite surface modification layer is formed by grafting a polydopamine transition layer onto a hexagonal boron nitride surface with dopamine hydrochloride, followed by grafting with 3-mercaptopropyltrimethoxysilane.

2. The cadmium-free and lead-free high thermal conductivity composite solder according to claim 1, characterized in that, The amount of gallium indium supported hexagonal boron nitride composite particles added is 1.6-2.2% of the total mass of the matrix alloy powder.

3. The cadmium-free and lead-free high thermal conductivity composite solder according to claim 1, characterized in that, The composite surface modification layer is made of a composite surface modifier, which includes 3-mercaptopropyltrimethoxysilane and dopamine hydrochloride, with a mass ratio of 3-mercaptopropyltrimethoxysilane to dopamine hydrochloride of 1:1.5-1:3.

0.

4. A method for preparing a cadmium-free and lead-free high thermal conductivity composite solder according to any one of claims 1 to 3, characterized in that, Includes the following steps:

1. Weigh Sn, Ag, Cu, Sb and Ni raw materials to prepare alloy melt; 2. Cool the alloy melt and atomize it to obtain a matrix alloy powder with a particle size of 15-40 μm; III. Preparation of gallium-indium supported hexagonal boron nitride composite particles, the specific steps of which include: (1) After hexagonal boron nitride is dispersed and ultrasonically exfoliated and dried, it is then dispersed in Tris buffer, dopamine hydrochloride is added, stirred at room temperature for 5-6 h, centrifuged and washed to obtain polydopamine-coated hexagonal boron nitride. (2) Add 3-mercaptopropyltrimethoxysilane to the solvent, adjust the pH to 4.5 with acetic acid, and pre-hydrolyze for 30 min; add polydopamine-coated hexagonal boron nitride, stir at 40 °C for 4 h, then centrifuge, wash and vacuum dry at 35 °C for 12 h; (3) Add gallium-indium alloy to a solvent to obtain a gallium-indium microdroplet dispersion; (4) The surface-modified hexagonal boron nitride was redispersed in a solvent; gallium indium microdroplet dispersion was slowly added under nitrogen protection and stirred for 1.5-2 h; after centrifugation, washing and drying, gallium indium supported hexagonal boron nitride composite particles were obtained.

4. Pre-disperse gallium indium supported hexagonal boron nitride composite particles in a solvent; add the matrix alloy powder to a nitrogen-protected mixer, and simultaneously add the gallium indium supported hexagonal boron nitride composite particle suspension to the mixer. After mixing, the material is dried and sieved to obtain cadmium-free and lead-free high thermal conductivity composite solder.

5. The method for preparing cadmium-free and lead-free high thermal conductivity composite solder according to claim 4, characterized in that, Step one is as follows: Weigh Sn, Ag, Cu, Sb and Ni raw materials and place them in a vacuum induction melting furnace. Evacuate the furnace to 30-80 Pa and maintain it for 5-15 min to remove air from the furnace. Under argon protection, raise the furnace temperature to 560-610 ℃. After the raw materials are completely melted, hold the temperature at 580-610 ℃ for 20-40 min, stir at a speed of 200-300 r / min for 10-15 min, and let it stand for 5-10 min to obtain the alloy melt.

6. The method for preparing cadmium-free and lead-free high thermal conductivity composite solder according to claim 4, characterized in that, In step two, the pressure of the atomizing gas is 2.0-4.5 MPa; the flow rate of the alloy melt is 5-20 kg / min; and the oxygen content in the atomization chamber is <500 ppm.

7. The method for preparing cadmium-free and lead-free high thermal conductivity composite solder according to claim 4, characterized in that, In step (1), the shearing process is carried out at 8000-12000 r / min for 25-30 min, and then ultrasonic treatment is carried out at 300-500 W with a 5 s on and 5 s intermittent mode for 2-3 h.

8. The method for preparing cadmium-free and lead-free high thermal conductivity composite solder according to claim 4, characterized in that, In step (4), gallium-indium microdroplet dispersion is slowly added under nitrogen protection for 20-30 min; after the addition is completed, stirring is continued at 250-300 r / min.

9. The method for preparing cadmium-free and lead-free high thermal conductivity composite solder according to claim 4, characterized in that, In step four, the composite particle suspension is slowly sprayed into the mixer over 20-30 minutes, and mixing continues for 35-45 minutes after the spraying is completed.